Akışkan yatakta ayrışma ve aglomerasyon rejimlerinin sıcaklık ölçümleri ile incelenmesi - Tolay, Mustafa (Fen Bilimleri Enstitüsü, 1994)
Akışkan yataklarda, linyitin kendisinden değişik yoğunluk ve tanecik boyutuna sahip bir yatak malzemesi içerisinde yakılması halinde ayrışma gerçekleşmektedir. Akışkan yataklı sistemlerde aglomerasyonun bir ön aşaması olarak beliren ayrışmanın mekanizması ve bunun aglomerasyona olan etkisinin anlaşılması yanmanın verimli ve sürekli olabilmesi açısından büyük önem taşımaktadır. Bu çalışmada, Göynük linyiti Şile kumu ve kuartz kumu içeren 0.11 m ve 0.2 m çaplarında akışkan yataklarda yakılmış ve sistemde yanmanın başlamasından aglomerasyonun gerçekleşmesine kadar geçirdiği ayrışma rejimleri incelenmiştir. Sistemler sürekli çalışacak şekilde tasarlanmıştır. Göynük linyiti ve sözü edilen yatak malzemelerinin tanecik boyutları dikkatli seçilerek akışkan yatakta bir uçta şiddetli linyit çöküşen zengin, diğer uçta da batışan zengin ayrışma karışımları elde edilerek çalışma gerçekleştirilmektedir. Akışkan yatakta linyit, inert komponente kıyasla çok düşük oranlarda bulunduğu için yatak içerisindeki dağılımı, yanma sonucu elde edilen sıcaklık dağılımından anlaşılabilir. Bu nedenle her iki akışkan yatakta dağıtıcı elekten 0.01, 0.03, 0.05, 0.1, 0.2 ve 0.3 m yükseklikteki seviyelere yerleştirilen ısıl çiftlerle ölçülen sıcaklık dağılımları tüm deney süresince izlenmiştir. Ayrışma rejimleri ve buna bağlı olarak gelişen aglomerasyonun belirlenmesinde diferansiyel sıcaklık değerleri kullanılmıştır. Ayrışma rejimleri için AT3, AT30 ve aglomerasyon için AT3A, AT30A olarak tanımlanan değerler anlamlı sonuçlar vermiştir. Bu değerlerin kontrol parametreleri olarak kullanılabileceği anlaşılmıştır. Deneylerin sonucunda akışkan yataklı linyit yakıcılarında yatağın normal şartlarda linyit yüzüşen zengin rejimde yandığı ancak yatak malzemesi tanecik boyutunun küçük, linyit tanecik boyutunun büyük seçilmesi ile linyit batışan zengin rejiminde sürdürülebileceği anlaşılmıştır. Değişen proses parametrelerinin ayrışma ve aglomerasyon üzerine etkileri incelenmiştir.

The beds in a binary lignite-bed material fluidised bed combustion system are forced to segregate. Measurement of bed segregation may be done by various methods: the bed may be slumped and the components can be vacuum collected and sieved, pressure drop and differential temperature readings may be measured. Also x-ray cine-photography and radioactive tracer techniques have been used for the determination of segregation patterns. Slumping the beds is a time consuming cumbersome method and, there is a tendency for ash particle size to be disturbed during sieving. The pressure measurement is a dynamic response but gives an overall picture of total bed, where as monitoring the segregation tendency through temperature readings gives representative information related to the number and location of thermocouples. Also, direct measurements of the bed temperature profiles can be provide useful information, since agglomeration is a thermal phenomenon which is depend on the sintering temperature of the bed. In a gas fluidised bed with more than one component the quality of fluidisation will be determined by the balance between mixing and segregation which are in turn determined by the densities and size differentials of the components. The fluidisation velocity affects the balance. The segregation tendency of the bed is attributed which tends to rise. This may be observed in a single component system where a particle size differential exists, or in multicomponent systems where there is density and/or particle size differential. For binary systems is a simple scheme, classifying the jetsam and flotsam components into three main groups, each having to subgroups. In case 1, where the particle sizes are - vm - similar, if the densities are also similar then the bigger component is jetsam la. If the densities are also similar then the bigger component is jetsam then the bigger component is jetsam lb. In case 2, when one particle size is much greater than the other, but the component with the smaller particle size is present in great excess, if the density of the larger particle is higher than that of the smaller then the component with larger particle size is jetsam 2a. If the density of the larger particle is less than that of the smaller, then the component with smaller particle size is jetsam 2b. In case 3 where one particle size is much greater than the other but the component with greater particle size is present in excess, if the component with greater particle size is denser than that of the smaller, then elutration of the smaller component may result jetsam 3a. If the component with greater particle size is less dense than that with the smaller, then either component may be jetsam 3b. In fluidised beds, when lignite is burned in a bed material of different density and particle size segregation occurs. Also segregation may occur in a single component system where there is a wide particle size distribution. Understanding of segregation systems which is a pre stage before agglomeration is necessary for efficient and continuous combustion. In this study, the processes taking place in fuidised bed combustion of Göynük lignite in Şile and quartz sands upto agglomeration is investigated. By choosing the particle sizes of Göynük lignite and bed material both extreme lignite jetsam and flotsam rich systems were obtained. The lignite used in this study was obtained from the Central Anatolia Lignite Works (Orta Anadolu Linyit İşletmeleri) at Göynük region. The lignite samples were crushed and classified into 1-2, 2-2.8, 2.8-4 and 4-5 mm fractions and kept in polyethylene bags. For elemental and ultimate analysis, calorific value, ash analysis and ash characteristics tests and experiments samples were grinded to -0.2 mm sizes. The lignite was burned in 0.11 m and 0.2 m diameter cylindrical continuous fluidised bed combustors. The smaller bed was heated by LPG burning at the freeboard which was later drawn into the bed as temperature of it was rised. For the start-up of the larger bed an automatic controlled two-stage heating system was designed and developed. - IX In this system the bed material was heated to 673 K via plenum chamber combustion of LPG and after this temperature the combustion was shifted to the bed upto the lignite combustion temperature by the automatic control system. In fluidised bed combustors the amount of the burning lignites are small compared to the inert bed material. For this reason the temperature profiles which reflects the heat evolution of the burning lignites is dependent and therefore can be used as a measure of the distribution of lignites in the bed. In order to monitor the temperature profiles continuous, thermocouples are located at 0.01, 0.03, 0.05, 0.1, 0.2 and 0.3 m from the distributor plate. From the temperature profiles, the temperature differential between the bed (0.1 m from the distributor plate) and 0.01 and 0.03 m were termed as ATj and AT3. These differential temperatures are found to be useful indicators of the degree of segregation or conversely mixing in the bed. Similarly, the temperature differential between the bed and 0.3 m from the distributor plate, AT30, is a measure of the segregation in the bed as reflected to the freeboard. Göynük lignites greater than 1-2 mm particle sizes in 0.1-0.4 mm or 0.4-0.7 mm Şile sand burned in a lignite jetsam rich segregating system. In lignite jetsam rich segregating system increasing the lignite particle size or decreasing the bed material size decreased ATj and AT3 and increased AT30. The reason for this behavior is the increasing tendency of the system as lignite jetsam which causes the lignite's to concentrate at the lower parts of the bed. Therefore, due to the heating of these parts AT3 decreased. At the same time, lignite combustion at the upper parts of the bed was decreased reflected as an increase on AT30. In this type of segregation beds, the reported combustion of lignite at the upper parts of the bed whilst combustion of volatile matter is found to be irrelevant. Changing the bed material with a denser material was observed to reduce the lignite jetsam segregation tendency. Similar to lignite jetsam rich segregation systems, the differential temperatures, AT3 and AT30, explained the segregation in a lignite flotsam rich type systems. This type of segregation was obtained for all particle sizes of lignite in q-sand. In this segregation system increasing the lignite particle size and/or decreasing the bed material particle size reduced the segregation tendency of the bed. Under these circumstances, AT} and AT3 were decreased and AT30 was increased. Changing the bed material to a denser material increased AT3 and decreased AT30. This is an increase in the tendency of the system towards lignite flotsam character. Therefore, combustion iş tending to concentrate towards the upper section of the bed. Whatever was the mode of segregation at the start of the experiments the system was observed to shift to a dynamic segregation equilibrium dictated by the lignite bed material density and/or particle size ratios. Increasing the fluidisation velocity increased the mixing intensity therefore decreased segregation for both kinds of segregation systems. Increasing the dynamic and static bed heights decreased the tendency of segregation due to the longer retention of bed material in the system. The bed diameter did not have a significant effect on segregation. During the course of dynamic settling of the segregation system the bed agglomerates if sintering temperature is reached at any point in the bed. It has been observed that the temperature differentials measured during agglomeration between the bed and 0.03 and 0.3 m from distributor plates were found to be useful parameters in the assessment of agglomeration with respect to segregation. These differential temperatures are termed as AT3A and AT3qa- Tag reflects the heat evolution at the time of agglomeration which is directly related to the concentration of lignite at this level whereas Tag is an indirect measure of lignite concentration in the bed. For lignite jetsam rich segregating systems an increase in lignite particle size or decrease in bed material particle size, AT3A was decreased and AT30A was increased. The increase in lignite particle size resulted in an increase in agglomeration temperature but a decrease in agglomeration time. The increase in agglomeration temperature was a result of the increase in sintering temperature while the increase in segregation was responsible for the decrease in the agglomeration time. For the lignite jetsam rich type segregation system as the segregation tendency increased the start of agglomeration in the bed shifted towards the distributor plate. For lignite flotsam rich type segregating systems as the lignite particle size was increased and/or bed material particle size was -XI decreased AT30A was decreased, AT3A was increased or were both decreased. Also with increased lignite particle size the agglomeration temperature and both increased. In this case the decrease in segregation was mainly responsible for the increase in agglomeration time while the increase in sintering temperature was responsible for the increase in agglomeration temperature. A reduction in the bed material particle size increased the agglomeration temperature. In this case the decrease in segregation tendency has a dominating effect over the effect of the bed material particle size on the reduction of sintering temperature. In lignite flotsam rich segregating systems, as the tendency of segregation increased the agglomeration started progressively at the upper parts of the bed. Also in this type of segregating beds a pure bed material (jetsam) layer was observed which was grossly lose from the agglomerate. The agglomeration times, At'^G? were found to be shorter for lignite jetsam systems compared with the flotsam systems, due to the increased combustion of lignites in the lower section the bed in the former case.
The Segregation systems leading of the agglomeration in fluidised bed combustor
Tez (Doktora)-- İTÜ Fen Bil. Enst., 1994
Keywords: Aglomerasyon; Akışkan yatak; Isı dağılımı; Isıtma sistemleri; Agglomeration; Fluidized bed; Heat distribution; Heating systems